ANALISA KEGAGALAN CONNECTING ROD MOBIL AVANZA VELOZ SERI MESIN K3-MC66021 - Sunaryo, Sunaryo; Hasan, Indra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2018)
The incident on the piston rod that experienced material failure occurred in the avanza 1500cc car. in the use of the car is not yet up to 1 year of use, the car was purchased in October 2015 and in April 2016 has been damaged in the area of the combustion chamber including connecting rod that experienced at the near end of the bing end, caused by many factors, it is necessary to test on the connecting rod to get the cause of the failure that occurred. Analyzes the failure of the connecting rod components by means of hardness testing, metalorgraphy testing and chemical composition testing. connecting rod analyzed is connecting rod car avanza veloz 1500CC. with material from the connecting rod is AISI 4340. from the results of hardness testing obtained an average hardness value of 125.9 VHN. As for the standard of violence on AISI 4340 the minimum value of violence that must be met is 228 VHN. Where the lowest hardness value of the component is 84.7 VHN. In microstructure testing, phases such as ferrite (light-colored), pearlit (dark color) and slightly cementite phase are found. While on testing the chemical composition of carbon (C) element is the lowest element that is equal to 0.23% with composition ratio on AISI 4340 steel with carbon content of 0.38% where viewed from the carbon content, the component belonging to low carbon steel causing failure this is the incompatibility of hardness value, chemical composition with AISI 4340 standard.